Sinus of Valsalva Aneurysm Rupture: An Unusual Presentation of Chromosome 22q11.2 Deletion: A Case Report - Eda-Cristina Abuchaibe; Nancy Dobrolet; Katherine Peicher; Roque Ventura; Elizabeth Welch (Hindawi Limited, 2012)
Sinus of Valsalva aneurysm (SVA) is defined as a weakness in the aortic valve wall, immediately above the attachments of each of the aortic cusps. This weakness can rupture and create an aortocardiac fistula. There are many congenital heart defects associated with chromosome 22q11 deletion, especially involving the aortic arch and its branches. SVA is not an anomaly usually associated with chromosome 22 deletion. We report the case of a 19-year-old female who presented to our institution with SVA rupture. She was subsequently diagnosed with chromosome 22q11 deletion syndrome. Despite dysmorphic facial features and a learning disability, our patient had not been diagnosed with the chromosome abnormality. SVA is a rare congenital heart defect and has only once previously been reported in a child with a chromosome 22q11 deletion. We report the first case where aneurysm rupture preceded the chromosomal findings. Chromosome 22q11 deletion could be missed due to either the unfamiliarity of physicians with the syndrome or the variability and subtlety of the phenotype. This was demonstrated by our patient who, at age 19 after presenting with an SVA rupture, prompted physicians to find an explanation for her coexisting dysmorphic features and her learning disability.